Direct hydrodeoxygenation of raw woody biomass into liquid alkanes - Qineng Xia (Nature Portfolio, 2016)
The conversion of renewable lignocellulosic biomass into liquid fuels is attractive but extremely challenging due to the inertness and complexity of lignocellulose. Here, the authors describe the direct hydrodeoxygenation of raw woods into liquid alkanes over a multifunctional Pt/NbOPO4catalyst.